Recent modifications of free gingival graft: A case series - Shah, Rucha (Contemp Clin Dent, 2015)
Free gingival grafts have been used in periodontal procedures to augment attached gingiva and cover denuded root surfaces. However, there are few limitations of the same such as esthetic mismatch, mal-alignment of muco-gingival junction formation and bulky appearance. Several modifications have recently been proposed to minimize some of the unfavorable aspects of free gingival grafts. Three cases presenting with Millers Class I/II gingival recession were treated by each different modifications. Satisfactory root coverage and better color match as a compared to free gingival graft was obtained in all the three cases. When indicated these modifications can be advantageous over conventional free gingival grafts in management of Millers Class I/II gingival recession.